PRAKTEK CUCI TANGAN PAKAI SABUN PADA SISWA SEKOLAH DASAR 05 NAGARI MUNGKA KABUPATEN LIMA PULUH KOTA - Elidahanum Husni; Sucy Ramadany (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2019)
Handwashing with soap is a healthy behavior scientifically proven to prevent the spread of infectious diseases such as diarrhea, upper respiratory tract infections (ISPA), and flu. Hand washing is one of the sanitation measures by cleaning the hands and fingers using running water and soap. School-age children are a period prone to various diseases. The habit of children consuming snacks freely, plus children not washing their hands with soap before eating, will cause various diseases. To avoid this, there is a need for counseling regarding washing hands with soap properly. The counseling was carried out on July 17, 2019, for class II 05 Mungka students with 25 students. The method used is counseling and demonstration of washing hands through 7 steps of washing hands with soap, according to the World Health Organization (WHO). Based on the preliminary study conducted, 05 Mungka Elementary School does not yet have adequate CPTS facilities and infrastructure and does not yet know the proper and correct CTPS practice steps. After conducting counseling activities in the form of education and demonstration of CTPS, increasing student knowledge related to the material provided can be seen from the evaluation of test results both pretest and post-test. So it can be concluded that this activity can increase the knowledge of the importance of washing hands using soap and students' ability to practice the seven steps of washing hands with soap properly. This aims to reduce student absenteeism due to illness caused by diseases.